2020
DOI: 10.1200/jco.2020.38.15_suppl.8008
|View full text |Cite
|
Sign up to set email alerts
|

Interim analysis of ZUMA-5: A phase II study of axicabtagene ciloleucel (axi-cel) in patients (pts) with relapsed/refractory indolent non-Hodgkin lymphoma (R/R iNHL).

Abstract: 8008 Background: Advanced stage iNHL, including follicular lymphoma (FL) and marginal zone lymphoma (MZL), is considered incurable as most pts experience multiple relapses (Wang, et al. Ther Adv Hematol. 2017), highlighting a need for novel therapies. Here, we present interim results from ZUMA-5, a Phase 2, multicenter study of axi-cel, an autologous anti-CD19 chimeric antigen receptor (CAR) T cell therapy, in pts with R/R iNHL. Methods: Adults with R/R FL (Grades 1-3a) or MZL (nodal or extranodal) after ≥ 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…In 80 patients with FL and 14 patients with marginal zone lymphoma that relapsed after 2 prior therapies, axi-cel treatment produced a 94% ORR with CR of 80%. 30 For the tisa-cel construct, similar FL responses were observed (80% ORR) with 60% of patients responding at 4 years. 8,23 Taken together, the limited long-term data suggest that remissions after anti-CD19 CAR-T in indolent lymphoma are durable.…”
Section: Cd19-directed Car T Cells For Fl and Marginal Zone Lymphomamentioning
confidence: 55%
See 1 more Smart Citation
“…In 80 patients with FL and 14 patients with marginal zone lymphoma that relapsed after 2 prior therapies, axi-cel treatment produced a 94% ORR with CR of 80%. 30 For the tisa-cel construct, similar FL responses were observed (80% ORR) with 60% of patients responding at 4 years. 8,23 Taken together, the limited long-term data suggest that remissions after anti-CD19 CAR-T in indolent lymphoma are durable.…”
Section: Cd19-directed Car T Cells For Fl and Marginal Zone Lymphomamentioning
confidence: 55%
“…Studies have demonstrated high response rates 8,9,23,30 and longterm remissions 8,9,23 after CAR-T administration for FL (Table 2). In 80 patients with FL and 14 patients with marginal zone lymphoma that relapsed after 2 prior therapies, axi-cel treatment produced a 94% ORR with CR of 80%.…”
Section: Cd19-directed Car T Cells For Fl and Marginal Zone Lymphomamentioning
confidence: 99%
“…CAR T is associated with CR rates up to 88% with sustained remission in up to 89% of FL patients with an initial response, over median follow-up of 28.6 months [ 234 236 ]. Recently presented data from the phase 2 ZUMA-5 trial which evaluated commercially available axicabtagene ciloleucel in patients with FL and MZL demonstrated ORR 94% (95% in FL, 86% in MZL), with CR rate of 79% [ 237 ]. While high-grade CRS and neurotoxicity remain concerns, occurring at rates of 13% and 28%, respectively, our growing experience utilizing appropriately-timed anti-cytokine blockade and corticosteroids should help mitigate severe toxicities [ 234 , 237 , 238 ].…”
Section: Relapsed and Refractory Diseasementioning
confidence: 99%
“…With a median follow-up of 11.5 months, 68% of patients had ongoing responses. CRS and ICANS occurred in 11% and 19% of patients ( 43 ). While the high response rates and manageable toxicities are promising in multiply recurrent FL, the length of follow-up in these trials is limited.…”
Section: Clinical Applications Of Car T-cell Therapy and The Role Ofmentioning
confidence: 99%